EVALUASI PROGRAM PENGEMBANGAN USAHA MINA PEDESAAN PERIKANAN BUDIDAYA DI KABUPATEN KONAWE SELATAN - Adam Azhar Amirullah (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2017)
This study aims to describe and analyze and evaluate PUMP for Aquaculture in Konawe Selatan District. While the aim of this program is to improve the business capacity of farmers, increase aquaculture production, increase farmers' income and welfare, absorb labor, develop entrepreneurship, strengthen institutional Pokdakan (Fisheries Cultivation Groups) and improve environmental quality. The research method used was descriptive qualitative with purposive sampling data collection techniques where the research subjects selected were people who understood and knew about this program. The focus of this research is effectiveness, efficiency, adequacy, alignment, responsiveness, and accuracy. The results of this study indicate that the PUMP of Aquaculture is effective and efficient because the production of aquaculture products increases compared to before the existence of this program and there is assistance by the PPK (Contract Fisheries Extension) who is the Contractor of the Ministry of Maritime Affairs and Fisheries. For the category of adequacy and leveling it can be said that it is not enough because there are only a few groups that get this PUMP assistance. As for responsiveness and accuracy, where this program is highly responded positively by groups of farmers and on target because recipients of assistance are true groups that work as a group of fisheries farmers.